2021
DOI: 10.1007/s13300-021-01166-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Flash Glucose Monitoring for the Management of Patients with Type 1 and Patients with Type 2 Diabetes in China

Abstract: Introduction: To compare the cost-effectiveness of flash glucose monitoring versus selfmonitoring of blood glucose/point of care testing (SMBG/POCT) in both patients with type 1 and patients with type 2 diabetes (T1D/T2D) receiving insulin therapy. Methods: The IQVIA CORE Diabetes Model (version 9.5) was used to project the lifetime costs and health outcomes of flash glucose monitoring and SMBG/POCT from a Chinese societal perspective. We considered both hospital and individual version flash glucose monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…5 A recent study which also used the IQVIA Core Diabetes Model, showed that isCGM was dominant compared to SMBG in China. 14 None of these studies estimated subgroupspecific ICERs, as we did in this study. The different time horizon and lower FSL costs could explain the more favorable ICER found in the Swedish study compared with our study.…”
Section: Discussionmentioning
confidence: 74%
“…5 A recent study which also used the IQVIA Core Diabetes Model, showed that isCGM was dominant compared to SMBG in China. 14 None of these studies estimated subgroupspecific ICERs, as we did in this study. The different time horizon and lower FSL costs could explain the more favorable ICER found in the Swedish study compared with our study.…”
Section: Discussionmentioning
confidence: 74%
“…In China, the individual version of flash glucose monitoring (Free-Style Libre; Abbott Diabetes Care, Witney, UK) is the most conventional type of CGMs for patients with T1DM caring out of hospitals. A recent research indicated that flash glucose monitoring could be considered as a cost-effective strategy compared with self-monitoring of blood glucose for Chinese T1DM patients receiving insulin therapy ( 40 ). Therefore, flash glucose monitoring can be a promising option to improve glycemic control in Chinese T1DM patients undergoing CSII therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had Type II diabetes without complications were assumed to have a baseline utility value of 0.785, which was obtained from Beaudet et al [ 25 ], and used as the default CDM value [ 26 ]. Quality of life utilities and disutilities associated with diabetes-related complications were obtained from Beaudet et al [ 25 ] and Zhao et al [ 27 ] ( Supplementary Table 1 ). The disutility associated with DKA [ 27 ] (0.0367) was obtained from a study of people with Type 1 diabetes experiencing DKA, as data on DKA disutilities in people with Type II diabetes could not be identified.…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life utilities and disutilities associated with diabetes-related complications were obtained from Beaudet et al [ 25 ] and Zhao et al [ 27 ] ( Supplementary Table 1 ). The disutility associated with DKA [ 27 ] (0.0367) was obtained from a study of people with Type 1 diabetes experiencing DKA, as data on DKA disutilities in people with Type II diabetes could not be identified. Based on the avoidance of daily and frequent fingerstick testing, an additional annual utility benefit of 0.03 (sourced from a time trade-off study [ 28 ]) was applied in the rt-CGM arm.…”
Section: Methodsmentioning
confidence: 99%